Vibration-assisted micro milling of AISI 316L produced by laser-based powder bed fusion. (November 2021) - Greco, Sebastian; Klauer, Katja; Kirsch, Benjamin; Aurich, Jan C.
Abstract: Additive manufacturing is suitable for the economical production of highly individual parts and components, but requires machining to produce surfaces of sufficient quality - as required on functional surfaces, for example. In many cases, the functionality of surfaces can be additionally enhanced by microstructuring e.g. via micro milling. The layered structure of additive manufactured materials, however, influences the process and process results of micro milling applications. In this paper it is analyzed whether the influence of the anisotropic material properties of additively manufactured workpieces can be compensated by vibration-assistance. Micro milling of additively produced AISI 316L with additional vibration-assistance is investigated. Besides the qualitative evaluation of tool wear, a quantitative analysis of the process forces, the surface roughness and the burr formation are used to evaluate the micro milling process. A significant influence of the vibration-assistance on the process forces and burr formation was observed.